Analisis Strategi Keamanan Nasional Indonesia dalam Menghadapi Ancaman Siber - Galang Ramadhan (Konstitusi : Jurnal Hukum, Administrasi Publik, dan Ilmu Komunikasi, 2025)
The rapid digital transformation has had a significant impact on various aspects of life, while simultaneously increasing the complexity of cyber threats faced by nations, including Indonesia. As a country with a high number of internet users, Indonesia is in a vulnerable position regarding cyberattacks that could threaten national stability. This study aims to analyze Indonesia’s national security strategy in responding to cyber threats through a descriptive qualitative approach based on literature review and document analysis. The findings show that Indonesia has implemented various strategic policies, including the establishment of the National Cyber and Crypto Agency (BSSN), the enactment of regulations such as the Personal Data Protection Law, as well as the strengthening of international cooperation, human resource development, and the utilization of security technologies. However, significant challenges such as weak inter-agency coordination, low digital literacy, and limited infrastructure remain major obstacles to effective implementation. This study recommends strengthening governance, increasing institutional capacity, and involving multiple stakeholders to build a national cybersecurity system that is adaptive, inclusive, and sustainable.